Budaya Tari Lengger dalam Perspektif Hukum Islam di Kabupaten Wonosobo) - Livia Setyawati (LPPM Institut Pesantren KH. Abdul Chalim, 2021)
Research on the culture of Lengger dance in the perspective of Islamic law aims to find out how the implementation of the Lengger dance is carried out by Muslims in Wonosobo Regency, to find out what factors cause the many fans of the Lengger dance in Wonosobo Regency, to find out how the view of Islamic law affects the Lengger dance as culture in Wonosobo Regency. This research uses a descriptive method. The data analysis technique used is qualitative analysis techniques. The results of the data from this article indicate that the Lengger dance culture is carried out on certain occasions, such as welcoming the Indonesian Independence Day, weddings, circumcisions, dreadlocks, etc. Lengger dance has developed until now, influenced by several historical, social, and economic factors. Most of the dancers and the people of Wonosobo are Muslim, in the implementation of the Lengger dance over time the meaning of philosophy in the lyrics or the Lengger dance is getting lost because what attracts dances with the beauty and courage of the dancer or just as entertainment. As the younger generation, they must preserve the culture and stick to Islamic law, namely restoring the religious and moral meaning of the Lengger dance and covering their genitals according to religious orders.